Maternal Exposure to Antidepressants Vilazodone and Vortioxetine: Effects on Neurodevelopment of Young Rat Offspring - Singh, K. P. (Asian Journal of Pharmaceutics (AJP), 2023)
Background: Vilazodone (VLZ) and Vortioxetine (VOX) are newer antidepressants often used for treating major depressive disorder, but potential therapeutic safety for brain development in pregnant women is almost negligible due to paucity of clinical and non-clinical data. Objectives: The current work was planned to investigate possible linkages between neurodevelopmental delay and prenatal exposure to equivalent therapeutic doses of VLZ and VOX. Materials and Methods: Pregnant Wistar rats were orally gavaged with VLZ and VOX (1 mg/kg, and 2 mg/kg body weight [BW]) from gestation day 6 to 21. The dams delivered naturally and reared their litters until postnatal day 21 during which neurodevelopment reflexes were recorded. Results: Prenatally VLZ-and VOX-exposed rats showed significant (1) reduction in BW, (2) delay in forelimb grasping, (3) delay in the day of apparition of cliff avoidance, (4) delay in response in negative geotaxis only in VOX group, (5) deficit in grip strength, and (6) delayed eye opening. Conclusion: Our findings suggest that early life exposure to VLZ and VOX might be involved in the retardation and maturation of some reflexes which imply an existing association between early life VLZ and VOX exposure with an increased risk of developmental vulnerability.